2006
DOI: 10.1007/s10853-006-7065-y
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a polyurethane scaffold for tissue engineering made by a combination of salt leaching and freeze-drying of dioxane

Abstract: Preparation of a polyurethane scaffold for tissue engineering made by a combination of salt leaching and freeze-drying of dioxane Heijkants, RGJC; Van Tienen, TG; De Groot, JH; Pennings, AJ; Buma, P; Veth, RPH; Schouten, AJ Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim. In the past several types of synthetic porous materials have been made as meniscus reconstruction material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 25 publications
1
41
0
Order By: Relevance
“…The production of porous structures via the removal of a pore forming or space holding (porogen) phase within a solid structure offers the greatest potential to control pore size and porosity whilst achieving a high level of pore homogeneity [14][15][16][17]. A number of researchers have used salt (NaCl) porogens in combination with several different processing methods to produce porous polymer structures: for instance, gas foaming [18]; concurrent electro-spinning [19], gas anti-solvent precipitation [20] and phase-separation [21], that tend to exhibit a wide range of irregularly-sized and shaped pores.…”
Section: Introductionmentioning
confidence: 99%
“…The production of porous structures via the removal of a pore forming or space holding (porogen) phase within a solid structure offers the greatest potential to control pore size and porosity whilst achieving a high level of pore homogeneity [14][15][16][17]. A number of researchers have used salt (NaCl) porogens in combination with several different processing methods to produce porous polymer structures: for instance, gas foaming [18]; concurrent electro-spinning [19], gas anti-solvent precipitation [20] and phase-separation [21], that tend to exhibit a wide range of irregularly-sized and shaped pores.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies we have characterized the frictional properties and resulting changes in tissue structure that occur with PUR meniscal scaffolds that have been used for soft tissue implants. [33][34][35][36][37][38][39] In these scaffolds, significant tissue ingrowth occurs in vivo [40][41][42][43][44][45][46] and this neocartilage may be Figure 8. Representative histological images of cartilage samples following articulation against PUR with PBS or ESF used as lubricants demonstrating surface damage and proteoglycan loss.…”
Section: Frictional Properties Of Porous Foamsmentioning
confidence: 99%
“…25 Of particular interest are porous polyurethane foams (PUR), which have been extensively evaluated as meniscal replacement materials. [33][34][35][36][37][38][39] PUR enables infiltration of cells into the material and subsequent generation of fibrocartilaginous tissue in in vivo rat and dog studies. [40][41][42][43][44][45][46] While these results are very promising, in PUR meniscal repair studies, cartilage damage similar to menisectomized controls was found over 6 months of implantation.…”
mentioning
confidence: 99%
“…In the last decade, various fabrication methods for construction of three-dimensional biomimetic scaffolds, including electrospinning, [1][2][3] phase-separation, 4,5 freeze drying, 6,7 and self-assembly, 8,9 have been developed for tissue engineering and regenerative medicine. These scaffolds can mimic the architecture of the native extracellular matrix at the nanoscale level (eg, hierarchical architecture formed with nanofibers and nanopores), which provides the initial space for regeneration of new tissue.…”
Section: Introductionmentioning
confidence: 99%